PEMANFAATAN LIMBAH KULIT ARI KULIT ARI INDUSTRl RUMAHAN TEMPE MENJADI PUPUK GRANUL TAHUN 2014 - Intan Anggun Permata WWY; Darjati .; Marlik . (Poltekkes Kemenkes Surabaya, 2014)
Organic fertilizer is fertilizer made from organic materials such as leaves, twigs, and livestock manure sobetter keep the soil fertile than inorganic fertilizers . One form of organic fertilizer is granule shapedfertilizers. Among the materials that can be made into organic fertilizer epidermal skin of soy generated byhome industries producing soybean cakes. The protein content of soybean epidermal skin is good for plantgrowth. The purpose of this research is to utilize soybean skin into fertilizer granules.This study followed a pre-experimental Post Test Only Design involving measurement after treatments.Data collection was performed by measurements and laboratory testing . Data were analyzed descriptivelyin reference to the Minister of Agriculture decree No.28 I Permentan I SR.130 /2009.Results of the study especially on the examination of the C / N ratio was 14.40 and water content ofgranular fertilizer was 24.80 % . It was pointed out that these results were not in accordance with the theMinister of Agriculture Regulation No.28 / Permentan/ SR.130/ 2009 on Minimum Technical RequirementsOrganic Fertilizer. Reduction of the C / N ratio was caused by the composting process that run longer.That's becausethe decomposition processeswere uneven that impacted on the finished compost . Fertilizercan still be used as a soil conditioner as the C I N ratio was in accordance with the regulations on theMinimum Technical Organic Soil conditioners but it requires additional drying so that the water content ofthe fertilizer falls within the standard that is 4-15 % .It is recommended especially for the owner of a home industries to process soybean husks into fertilizer foradditional earnings and incomes. Farmers should start getting used to using organic fertilizers inagriculture. Future researchers should perform aeration during the composting process so that compost canmature completely perfectly and evenly . Educational institutions may use results of this study as aninnovative practice, especially in the areas of soil health and waste management